2022
DOI: 10.1038/s42949-022-00066-w
|View full text |Cite
|
Sign up to set email alerts
|

Human mobility and infection from Covid-19 in the Osaka metropolitan area

Abstract: Controlling human mobility is thought to be an effective measure to prevent the spread of the COVID-19 pandemic. This study aims to clarify the human mobility types that impacted the number of COVID-19 cases during the medium-term COVID-19 pandemic in the Osaka metropolitan area. The method used in this study was analysis of the statistical relationship between human mobility changes and the total number of COVID-19 cases after two weeks. In conclusion, the results indicate that it is essential to control the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The results supported the analysis in the case of a suburban city in the Osaka metropolitan area (Kato and Matsushita, 2021). In the Osaka metropolitan prefectures, transit stations had little correlation with the number of infections (Kato and Takizawa, 2022b). These results suggest that encouraging walking and public transit use decreased medical costs in metropolitan prefectures during the pandemic.…”
Section: Discussionsupporting
confidence: 74%
“…The results supported the analysis in the case of a suburban city in the Osaka metropolitan area (Kato and Matsushita, 2021). In the Osaka metropolitan prefectures, transit stations had little correlation with the number of infections (Kato and Takizawa, 2022b). These results suggest that encouraging walking and public transit use decreased medical costs in metropolitan prefectures during the pandemic.…”
Section: Discussionsupporting
confidence: 74%
“…However, the human mobility of public transit decreased after November 2020. In the Osaka metropolitan prefectures, it was found that the human mobility of transit station had little correlation with the number of infected cases [33]. These results suggest that encouraging walking and public transit would reduce medical costs in metropolitan prefectures during the pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…The authors also declared groceries and pharmacies were the sources of infection, but the transit station was not. Inconsistent with Kato and Takizawa, 2022 , Steiger et al, 2021 argued that the increase in mobility at groceries and pharmacies correlated to the low newly reported cases. Further, their study also reported mobility at retail and recreational areas or workplaces positively affected the rise of infection.…”
Section: Introductionmentioning
confidence: 92%
“…Meanwhile, studies by Lee et al, 2021 , Tribby and Hartmann, 2021 indicated green areas and parks negatively related to the low infected case in the U.S. and England. By contrast, Kato and Takizawa (2022) claimed that visits to parks were the determinant of the high risk. The authors also declared groceries and pharmacies were the sources of infection, but the transit station was not.…”
Section: Introductionmentioning
confidence: 98%